Analisis Kelasahan Siswa SMP dalam Menyelesaikan Soal Cerita Kontekstual Materi Kubus Ditinjau dari Gender - Shaula Rahma Pratiwi; Fatriya Adamura; Indra Puji Astuti (Universitas Veteran Bangun Nusantara, 2023)
Education is a common activity in human life. Every life in society has an educational process, both intentionally and unintentionally. In studying mathematics, students are required to be able to relate mathematical concepts that will later be useful in the process of solving problems. Students are expected to be able to master and apply mathematics subjects to daily life. This study aims to describe what mistakes male and female students often make in solving problems to build a flat side room. This study aims to describe what mistakes are often made by male students and. women in solving problems building flat side rooms. This type of research is descriptive qualitative. The subjects of this study were 2 female students and 2 male students of class VIII-A of SMP N 1 Sawahan for the 2021/2022 school year. Data collection techniques include written test questions and interviews. The data validity technique uses triangulation techniques, which aim to compare test result data and interview results. The data analysis technique uses three stages, namely data reduction, data presentation and conclusion.